Toxicological Impact of Agricultural Surfactants on Australian Frogs - Mann, Reinier Matthew (Curtin University, 2000)
Surfactants are one of the more ubiquitous contaminants in aquatic systems. Their importance as toxic components of pesticide formulations has, however, been largely overlooked. Amphibians particularly, as inhabitants of shallow, temporary and often lentic aquatic environments may be at risk from exposure to these chemicals when they enter aquatic systems. This thesis presents data on the toxicity of surfactants to amphibians. Several experimental exposures were conducted with embryo-larval, tadpole and adult developmental stages of the Australian species- Crinia insignifera, Helcioporus eyrei, Limnodynastes dorsalis and Litoria moorei and the exotic species- Bufo marinus and Xenopus laevis. Animals were variously exposed to glyphosate formulations that contain a high proportion of nonionic surfactants, or commercial pesticide wetting agents (alcohol alkoxylate and nonylphenol ethoxylate (NPE) surfactants). Feeding stage tadpoles of C.insignifera, H. eyrei, L. dorsalis and L. moorei were exposed to three commercial glyphosate formulations, glyphosate isopropylamine and glyphosate acid in static-renewal acute toxicity tests. The 48-h LC50 values for Roundup Herbicide (MON 2139) tested against tadpoles of C. insignifera, H. eyrei, L. dorsalis and L. moorei ranged between 8.1 and 32.2 mg/L (2.9 and 11.6 mg/L glyphosate acid equivalent (ae)), while the 48-h LC50 values for Roundup Herbicide tested against adult and newly metamorphosed C. insignifera ranged from 137-144 mg/L (49.4-51.8 mg/L ae).Touchdown Herbicide (4 LC-E) tested against tadpoles of C. insignifera, H. eyrei, L. dorsalis and L. moorei was slightly less toxic than Roundup with 48-h LC50 values ranging between 27.3 and 48.7 mg/L (9.0 and 16.1 mg/L ae). Roundup Biactive (MON 77920) was practically non-toxic to tadpoles of the same four species producing 48-h LC50 values of 911 mg/L (328 mg/L ae) for L. moorei and >1000 mg/L (>360 mg/L ae) for C. insignifera, H. eyrei and L. dorsalis. Glyphosate isopropylamine was practically non-toxic producing no mortality amongst tadpoles of any of the four species over 48 h, at concentrations between 503 and 684 mg/L (343 and 466 mg/L ae). The toxicity of technical grade glyphosate acid (48-h LC50, 81.2-121 mg/L) is likely to be due to acid intolerance. Feeding stage tadpoles of B. marinus, X laevis, C. insignifera, H.eyrei, L. dorsalis and L. moorei were exposed to NPE and alcohol alkoxylate in static renewal acute toxicity tests. All species exhibited non-specific narcosis following exposure to both these surfactants. The 48-h EC50 values for NPE ranged between 1.1 mg/L (mild narcosis) and 12.1 mg/L (full narcosis). The 48-h EC50 values for alcohol alkoxylate ranged between 5.3 mg/L (mild narcosis) and 25.4 mg/L (full narcosis). Xenopus laevis was the most sensitive species tested. The sensitivity of the other five species was size dependent with larger species displaying greater tolerance. Replicate acute toxicity tests with B. marinus exposed to NPE at 30 degrees celsius over 96 hours indicated that the narcotic effects were not particularly time dependant.The mean 24, 48, 72 and 96-h EC50 (mild narcosis) were 3.6, 3.7, 3.5 and 3.5 mg/L respectively. The mean 24, 48, 72, and 96-h EC50 (full narcosis) values were 4.0, 4.1, 4.2 and 4.0 respectively. Acute toxicity tests with B. marinus exposed to NPE at 30 degrees celsius under conditions of low dissolved oxygen (0.8-2.3 mg/L) produced a two to threefold increase in toxicity. The 12-h EC50 values ranged from 1.4 to 2.2 mg/L. The embryotoxicity of NPE was determined in X. laevis, L. adelaidensis and C. insignifera using a Frog Embryo Teratogenesis assay-Xenopus (FETAX). The 96-h LC50, EC50 and MCIG (LOEC) values for X. laevis were 3.9 to 5.4 mg/L, 2.8 to 4.6 mg/L and 1.0 to 3.0 mg/L respectively. The 140-h LC50, ECSO and MCIG values for L. adelaidensis were 9.2 mg/L, 8.8 mg/L and 5.1 to 6.0 ing/L respectively. The 134-h LC50, EC50 and MCIG values for C. insignifera were 6.4 mg/L, 4.5 mg/L and 4.0 mg/L respectively. Teratogenicity indices for the three species ranged between 1.0 and 1.6 indicating either no or low teratogenicity. Xenopus laevis was the more sensitive of the three species and the only species that displayed indisputable terata. The acute toxicity data indicated that the amphibian species tested were of similar sensitivity to fish and some invertebrates. Developmental retardation and oestrogenic effects following exposure to nonylphenol ethoxylate were indicated by sublethal toxicity tests. Crinia insignifera embryos were exposed during early embryogenesis to sublethal concentrations of NPE.Exposure to NPE did not affect either weight nor size (snout-vent length) at metamorphosis. Exposure to 5.0mg/L NPE resulted in a significant delay in the time required to reach metamorphosis. Also, exposure to 3.0 mg/L NPE for the first 6 days of embryonic development or exposure to 5.0 mg/L NPE from day 2 to day 6 resulted in a statistically significant predominance in the female phenotype amongst metamorphosing froglets. Exposure for the first five days to 1.5 ing/L or 3.0 mg/L NPE had no effect on sex ratio. The results indicated that exposure to NPEs has endocrine disruptive effects in this species and that a narrow window of susceptibility exists for the induction of predominantly female phenotype. This study has also followed the degradation of a mixture of NPE oligomers and the concomitant formation of individual oligomers in static die-away tests with and without illumination in freshwater. Over 33 days in darkness there was a progressive and complete loss of long chain oligomers (NPEO(subscript)8-17), transient increases and subsequent loss of short to medium chain oligomers (NPE0(subscript)4-7), and large persistent increases (approximately 1000%) in short chain oligomers (NPE0(subscript)1-3). In the presence of illumination, biodegradation was retarded and heterotrophic bacterial proliferation was inhibited. After 33 days there was complete loss of long chain oligomers (NPE0(subscript)9-17), incomplete loss of medium chain oligomers (NPE0(subscript)6.8) and increases in short chain oligomers (NPE0(subscript)1-5).This thesis discusses the importance of persistent metabolites of NPE degradation as it pertains to the habitat, developmental time frame and ecology of amphibians. Degradation of NPE is likely to occur over a time frame that is longer than that required for complete embryogenesis and metamorphosis of many species of amphibians, and may easily encompass those critical stages of development during which oestrogenic metabolites can affect development.